PERANCANGAN PRODUCT LIFE STYLE DENGAN MOTIF BATIK YANG MEMILIKI FILOSOFI TENTANG POTENSI KEHIDUPAN PENYANDANG KELAINAN GENETIS - Dian Iqbal Fanani; Maria Goretti Marianti P.; Wyna Herdiana (Perpustakaan Universitas Surabaya, 2018)
Genetic diseases or genetic disorders are a condition caused by abnormalities by one or more genes that cause a clinical phenotype condition or in simpler language is a deviation from the general nature or nature of the average human being, and is a disease that arises due to malfunctioning factors - genetic factors that regulate the structure and physiological functions of the human body. In this study, the potential lives of people with genetic disorders will be used as a philosophy in batik with new motives. The purpose of this study is to provide education containing a moral message about the potential life of people with genetic disorders to the wider community in a new way, namely beredukasi through batik and then be applied to life style products. The method used in this report is qualitative method in the form of interview result, and quantitative method in the form of series of experimental process. From the experiments conducted is to provide alternatives to the molecular form stilasi process to parties who know about biology. Taking the concept of molecular form due to genetic disorder the factor is its molecules, such as DNA, proteins and chromosomes. Then choose the alternative form of stylation to be the design process isen and batik. On Selection of batik products to conduct interviews to owners of SMEs Batik to get advice. And finally the selected product is shoes. Shoes are designed in the form of